Preservation and storage of high-moisture grain with propionic acid (Revised 1975) - Hicks, Dale R.; Johnson, H. G.; Cloud, Harold A.; Christensen, C. M.; Meronuck, R. A. (University of Minnesota. Agricultural Extension Service, 1975)
This archival publication may not reflect current scientific knowledge or recommendations. Current information available from the University of Minnesota Extension: https://www.extension.umn.edu.
1 online resource (PDF, 2 pages)